Essential Issues in SOC Design Designing Complex Systems-on-Chip - Lin, Youn-Long Steve; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book originated from a workshop held at the DATE 2005 conference, namely Designing Complex SOCs. State-of-the-art in issues related to System-on-Chip (SoC) design by leading experts in the fields, covers IP development, verification, integration, chip implementation, testing and software. SOC design is fast becoming the key area of focus that engineers and researchers from the Electronic Design Automation field are focusing on in their quest to further develop Integrated Circuit technology. The more systems and even networks that we can integrate on one piece of silicon, the faster, cheaper, more powerful and efficient the technology will become. Essential Issues in SOC Design contains valuable academic and industrial examples for those involved with the design of complex SOCs, all contributors are selected from a region of the world that is generally known to lead the "SOC-Revolution", namely Asia.
Keywords: ENGINEERING; ENGINEERING DESIGN; ELECTRONICS; TELECOMMUNICATION; SYSTEMS ENGINEERING; NANOTECHNOLOGY; ENGINEERING; CIRCUITS AND SYSTEMS; ELECTRONIC AND COMPUTER ENGINEERING; COMMUNICATIONS ENGINEERING, NETWORKS; ELECTRONICS AND MICROELECTRONICS, INSTRUMENTATION; ENGINEERING DESIGN; NANOTECHNOLOGY